Clinical significance of pulse pressure in patients with heart failure with preserved left ventricular ejection fraction. (15th May 2016) - Tokitsu, Takanori; Yamamoto, Eiichiro; Hirata, Yoshihiro; Kusaka, Hiroaki; Fujisue, Koichiro; Sueta, Daisuke; Sugamura, Koichi; Sakamoto, Kenji; Tsujita, Kenichi; Kaikita, Koichi; Hokimoto, Seiji; Sugiyama, Seigo; et al.
Abstract: Aims: Although pulse pressure (PP) is a recognized risk factor for various cardiovascular diseases, its association with cardiovascular outcomes in patients with heart failure with preserved ejection fraction (HFpEF) is uncertain. Methods and results: We enrolled 512 of 951 consecutive HFpEF patients admitted to the Kumamoto University Hospital between 2007 and 2013 and divided them into five groups according to PP quintiles. Blood pressure and pulse wave velocity (PWV) were measured by an ankle–brachial index device. The PP values in HFpEF were significantly and positively correlated with PWV and LV stroke volume index, and were negatively correlated with estimated glomerular filtration rate and haemoglobin levels. Furthermore, plasma B‐type natriuretic peptide levels in HFpEF patients with the lowest (<45 mmHg) and highest PP (≥75 mmHg) were significantly higher than those with other PP (45–74 mmHg). The percentage of total cardiovascular and heart failure (HF)‐related events by PP category resulted in U‐ and J‐shaped curves. The higher frequency of coronary‐related events was nearly linear. In the Kaplan–Meier analysis, HFpEF patients with the lowest and highest PP quintiles had a significantly higher risk of cardiovascular and HF‐related events than those with other PPs (45–74 mmHg) (log‐rank test, both P < 0.01). Conversely, the frequency of coronary‐related events in the highest PP group, but not in the lowest PP group, was significantly higher than in other PP groups. Conclusion: Pulse pressure lower than 45 mmHg and higher than 75 mmHg was closely associated with HFpEF prognosis, indicating the clinical significance of PP for risk stratification of HFpEF.